2018
DOI: 10.1111/cmi.12963
|View full text |Cite
|
Sign up to set email alerts
|

On‐site secretory vesicle delivery drives filamentous growth in the fungal pathogenCandida albicans

Abstract: Candida albicans is an opportunistic fungal pathogen that colonises the skin as well as genital and intestinal mucosa of most healthy individuals. The ability of C. albicans to switch between different morphological states, for example, from an ellipsoid yeast form to a highly polarised, hyphal form, contributes to its success as a pathogen. In highly polarised tip-growing cells such as neurons, pollen tubes, and filamentous fungi, delivery of membrane and cargo to the filament apex is achieved by long-range d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 73 publications
1
22
1
2
Order By: Relevance
“…Recent findings suggest that the organization of the secretory pathway facilitates optimized trafficking of secretory vesicle to the hyphal tip. In this model, the ER and Golgi move into the extending filament allowing reduced distances of travel within the tip region for secretory vesicle delivery [322]. Polarized secretion starts with a stream of vesicles accumulating in Spitzenkörper [323,324], an organelle of clustered vesicles that provides the material for hyphal growth [322].…”
Section: Polarized Secretion In Candida Albicans Hyphaementioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings suggest that the organization of the secretory pathway facilitates optimized trafficking of secretory vesicle to the hyphal tip. In this model, the ER and Golgi move into the extending filament allowing reduced distances of travel within the tip region for secretory vesicle delivery [322]. Polarized secretion starts with a stream of vesicles accumulating in Spitzenkörper [323,324], an organelle of clustered vesicles that provides the material for hyphal growth [322].…”
Section: Polarized Secretion In Candida Albicans Hyphaementioning
confidence: 99%
“…In this model, the ER and Golgi move into the extending filament allowing reduced distances of travel within the tip region for secretory vesicle delivery [322]. Polarized secretion starts with a stream of vesicles accumulating in Spitzenkörper [323,324], an organelle of clustered vesicles that provides the material for hyphal growth [322]. Vesicles are then recruited by the polarisome and transported to the cell surface before they dock at the plasma membrane, facilitated by components of the exocyst complex and subsequent delivery of its cargo by SNARE-mediated membrane fusion [233].…”
Section: Polarized Secretion In Candida Albicans Hyphaementioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanics of hyphal elongation are thought to be broadly similar in C. albicans hyphal cells and in filamentous fungi, there are, nonetheless, some significant differences: for example, the C. albicans hyphae extension is relatively slower and does not appear to require microtubules, although it does still require the actin cytoskeleton [51,52]. Furthermore, while C. albicans hyphae also have a Spitzenkörper near the apex [53], a recent report concludes that the travel of most secretory vesicles is short-range, compared to that in typical filamentous fungi [54].…”
Section: Mechanism Of Hyphal Morphogenesismentioning
confidence: 99%
“…Electron micrographs of U. maydis filamentous cells indicate the presence of a few, similarly sized, vesicles in the apical region ( Lehmler et al, 1997 ), which would explain the joint delivery of Gsc1p, Chs6p and Msc1p. More recently, it has been shown that the SPK of C. albicans contains also homogenously sized secretory vesicles ( Weiner et al 2019 ), suggesting that co-delivery of cell wall synthesizing enzymes could also occur in this and other fungal species. However, as cellular and biochemical evidence from N. crassa and other species indicate ( Fajardo-Somera et al, 2015 , Riquelme et al, 2014 , Sánchez-León et al, 2015 , Schultzhaus et al, 2015 , Verdín et al, 2009 ), co-delivery is not a general secretion mechanism of cell wall synthesizing enzymes .…”
Section: Behind the Scenes To A Successful Destination: The Path Of Tmentioning
confidence: 99%